Literature Review: Risk Factos Affecting College Student's Mental Disorder During Covid19 Pandemic - Shofiyah Salma Farumi (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: The pandemic of coronavirus disease 2019 has become a real hazard and affects many sectors, one of them is education. The high number of new cases has made several countries to implement lockdown and quarantine policies. This policy caused several schools and universities to be closed to break the chain of transmission. Besides, the indirect effect of COVID19 is the mental disorder of the society, including students, that is getting worse. Mental disorder has become a growing health problem and requires more attention. This study aimed to explore the risk factors affecting students' mental disorder at the period of the COVID19 pandemic based on the previously performed research from published journals. Discussion: Of the 394 literature that has been searched in Pubmed and Science Direct, by entering the keywords of coronavirus, mental disorder, education, and universities, it obtained 7 articles in accordance with inclusion criteria. The inclusion criteria in this study included articles published in 2019 and 2020, articles categorized as original research articles, articles written in English, and articles discussed mental disorder in students since the COVID19 pandemic. The results of the study showed that in countries with quite high COVID19 cases, the risk factors affecting students' health were news about new case rates, mortality rates, and COVID19 cure rates. Conclusion: Mental disorder disorders experienced by students during the pandemic were anxiety, stress, and depression. For further research, it is expected to provide recommendations for activities that can prevent students' mental disorder to not worse during the pandemic.